A comparison of actual and theoretical treatments of glenoid fractures. Issue 4 (April 2015) - Mulder, Frans J.; van Suchtelen, Mark; Menendez, Mariano E.; Gradl, Gertraud; Neuhaus, Valentin; Ring, David
Abstract: Background: There is no consensus on the operative treatment of glenoid fractures. The purpose of this study was to see whether there was a difference between how patients with a glenoid fracture would receive treatment according to theoretical operative indications based on the measurement of computed tomography (CT) scans and radiographs and the treatment they actually received in our institutions. Methods: A total of 457 patients with a scapular fracture were treated in two level 1 trauma centres between January 2002 and August 2011. Ninety-eight patients with a glenoid fracture were retrospectively analyzed. Intra-articular gap, medial or lateral (M/L) displacement, angular deformity, and glenopolar angle (GPA) were measured on CT scans or radiographs to determine theoretical indications for operative treatment. Results: Twenty-four patients (25%) actually had operative treatment, while 35 patients (36%) fulfilled at least one theoretical criterion to proceed with operative treatment with a medium correlation between theoretical indications for surgery and the actual operative treatment. All the patients with a theoretical indication for surgery had an intra-articular gap with a step-off of >4 mm. A bony Bankart lesion with shoulder dislocation and injury in sports was retained in the best multivariable model as indications for the actual surgery. Conclusion: Theoretical guidelines for surgery on glenoid fractures may not have much influence on the current treatment. Level of evidence: Therapeutic, level III.